Gastric remnant cancer patients had a better prognosis than upper-third gastric cancer patients in a case-control study after surgical treatment. Issue 4 (July 2013) - Li, Fangxuan; Zhang, Rupeng; Liang, Han; Quan, Jichuan; Liu, Hui; Zhang, Hui
Background: The aim was to compare the clinicopathological features and prognostic outcomes of gastric remnant carcinoma patients with those of patients with upper-third gastric cancer. Methods: Clinical data extracted from 112 gastric remnant carcinomas and 367 upper-third gastric cancer patients were analyzed to explore the clinicopathologic differences between two groups. After radical resection, prognostic difference between them was evaluated through a 1:2 matched case-control study. Results: The pattern of gastric remnant carcinomas showed a male predominance. Undifferentiated type histology, depth at T4 stage and distant metastases were more frequent in gastric remnant carcinomas than in upper-third gastric cancers (P <0.05). The radical resectability of gastric remnant carcinomas was lower and the multi-visceral resectabilitiy was relatively higher than the other group (P = 0.00). Gastric remnant carcinomas trended to have a higher incidence of metastases to either mesojejunum or lower mediastinal lymph nodes than upper-third gastric cancers, but patient survival was not significantly different. In the case-control study, gastric remnant carcinomas had a better prognosis than upper-third gastric cancers after radical resection when the clinicopathologic features and surgical treatment were matched. Conclusions: Although there was no significant prognostic distinction between gastric remnant carcinomas and upper-third gastric cancer, after radical surgical treatment, patients with the former had an even better prognosis.